Business Environment Affecting Human Capital Development in the Digital Era of small and medium enterprises in Nonthaburi Province - Prayoonvong, Nachon (Journal of Humanities and Social Sciences, Rajapruk University, 2023)
The purposes of this research were to 1) study the importance of human capital development in the digital age of small and medium enterprises 2) study the internal environment that affects human capital development in the digital age of small and medium enterprises and 3) study the environment outside the organization that affects human capital development in the digital age of small and medium enterprises. A sample were entrepreneurs in small and medium enterprises, trading business, manufacturing business, service business, and agribusiness located in Nonthaburi Province. There were 400 respondents to a questionnaire and 24 respondents to an interview Data were collected using a questionnaire and structured interviews and analyzed through frequency, percentage, mean, Standard Deviation and Multiple Regression Analysis. The research results showed that; 1) The most organizations focused on human resource management in the organization’s management strategy. The ability of SMEs depended on human resources management in accordance with business strategies in order to create a sustainable competitive advantage of the organization.2) the internal environment on organizational strategy, system, skills, knowledge, competence, and shared values aspect affected human capital development at the highest level. 3) The external environment on politic, economic, social and cultural, and technological aspects affected human capital development at the highest level. There was a statistically significant difference at the .05.